An extensıon of ratıonal contractıve condıtıon ın partıally ordered rectangular metrıc spaces - Kır, Mehmet; Aktürk, Mehmet Ali; Dutta, Hemen; Yolacan, Esra (MISKOLC MATHEMATICAL NOTES, 2017)
In this paper, we discuss the concept of partially ordered rectangular metric spaces using the notation .X; ; d/. Also, we give a generalized contractive condition in the context of partially ordered rectangular metric space for all comparable p
Keywords: Fixed point; Rectangular metric; Generalized metric spaces